2010
DOI: 10.1158/0008-5472.can-09-3644
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead Box F1 Regulates Tumor-Promoting Properties of Cancer-Associated Fibroblasts in Lung Cancer

Abstract: Cancer-associated fibroblasts (CAF) attract increasing attention as potential cancer drug targets due to their ability to stimulate, for example, tumor growth, invasion, angiogenesis, and metastasis. However, the molecular mechanisms causing the tumor-promoting properties of CAFs remain poorly understood. Forkhead box F1 (FoxF1) is a mesenchymal target of hedgehog signaling, known to regulate mesenchymalepithelial interactions during lung development. Studies with FoxF1 gain-and loss-of-function fibroblasts re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 48 publications
1
68
0
Order By: Relevance
“…During embryonic and fetal periods, FOXF1 drives migration (26) and myofibroblastic differentiation (38) of lung mesenchyme. In our experiments, FOXF1 did not induce myofibroblast differentiation in adult lung fibroblasts since FOXF1 did not influence ␣-smooth muscle actin expression.…”
Section: Discussionmentioning
confidence: 99%
“…During embryonic and fetal periods, FOXF1 drives migration (26) and myofibroblastic differentiation (38) of lung mesenchyme. In our experiments, FOXF1 did not induce myofibroblast differentiation in adult lung fibroblasts since FOXF1 did not influence ␣-smooth muscle actin expression.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, many of these CAF-markers are functionally related to matrix remodeling, autophagy, senescence, ketone production, hypoxia, oxidative stress, inflammation, DNA damage, and stemness, 22 as well as FGF/EGF/PDGF-signaling. 23,24 These similarities also include molecular markers of the myofibroblast phenotype (such as, actin-binding proteins, the myosins, and other muscle proteins) 22 ( Table 5).…”
Section: 32e-05mentioning
confidence: 99%
“…Recently it was shown that the forkhead box transcription factor FOXF1 is a target of the TP53 family and its ectopic expression inhibits cancer cell invasion and migration, whereas the inactivation of FOXF1 stimulated both these processes [28,35]. Furthermore, this transcription factor is a mesenchymal target of hedgehog signaling, known to regulate mesenchymal-epithelial interactions during lung development and contractility of fibroblasts, their production of hepatocyte growth factor and fibroblast growth factor-2 as well as their stimulation of lung cancer cell growth and migration [36].…”
Section: Hypoxia As Well As the Endoplasmic Reticulum Stress Are Impomentioning
confidence: 99%